The Cerebellar Neuropsychiatric Rating Scale: a new card in the deck - Fritze, Stefan; Ferrucci, Roberta; Manto, Mario U. (The cerebellum, 2025)
Research on the cerebellum has come a long and impressive way. While traditionally assumed as only engaged in motor control, rediscovery of early literature reports and recent studies also point to the cerebellum´s role in vestibular and cognitive affective functioning at the frontiers of psychiatry. Indeed, damage to the cerebellum often leads to consequences in cognitive affective functioning, including deficits in executive, visuo-spatial and linguistic functioning as well as affect regulation. However, in order to further disseminate these scientific advances and to provide palpable progress to clinicians, smart tools that can be applied in daily clinical practice need to be developed. In particular, rating scales, which remain the most robust clinical method in the assessment of cerebellar patients, need to be developed. Although neuropsychiatric symptoms of cerebellar disease are common, they do not conform to DSM-5 diagnostic categories of psychiatric disorders. The Cerebellar Neuropsychiatric Rating Scale (CNRS), an informant-based questionnaire reported by Daly et al., may fill this gap, allowing clinicians for the first time to capture and quantify neuropsychiatric symptoms that have often been overlooked in ataxias in the past. The CNRS may represent a reliable instrument in ataxias. The scale offers a promising tool for early detection and targeted intervention, fostering interdisciplinary collaboration between neurologists, psychiatrists, and psychologists. Future developments may refine its clinical applicability, expand its use to other neurological disorders, and integrate digital health solutions to enhance real-world assessment and treatment.
Gesehen am 21.07.2025